Association of SP1 rs1353058818 and STAT3 rs1053004 gene polymorphisms with human tongue squamous cell carcinoma. Issue 7 (23rd July 2019) - Lai, Heqing; Xu, Guochao; Meng, Haifeng; Zhu, Haiying
Abstract : Objective: To study the association between SP1 rs1353058818 and STAT3 rs1053004 gene polymorphisms and risk of human tongue squamous cell carcinoma (TSCC). Methods: Sanger sequencing was used to determine the genotypes of SP1 rs1353058818 and STAT3 rs1053004 loci in 240 TSCC patients and 240 controls. Levels of hsa-miR-149-5p and hsa-miR-21-5p and expression levels of SP1 and STAT3 proteins in tumor tissues and adjacent normal tissues of TSCC patients were ascertained. Results: Carrying the SP1 rs1353058818 locus deletion allele was a high risk factor for TSCC (OR = 2.997, 95% CI: 1.389–6.466, P = 0.003). The STAT3 rs1053004 locus A allele was a protective factor for TSCC (OR = 0.604, 95% CI: 0.460-0.793, P < 0.001). There was a negative correlation between SP1 mRNA and hsa-miR-149-5p in tumor and adjacent normal tissues ( r = −0.81, −0.77). The expression of SP1 protein in tumor tissues of the SP1 rs1353058818 locus DD genotype was significantly higher than in tissues of the ID type, and in tissues of type II it was the lowest. STAT3 mRNA was positively correlated with hsa-miR-21-5p in tumor and adjacent normal tissues ( r = 0.75, 0.78). The expression level of STAT3 protein in tumor tissues of patients with STAT3 rs1053004 locus GG genotype was significantly higher than in patients with type GA, and it was the lowest in patients with type AA. Conclusion: Polymorphisms in the SP1 rs1353058818 and STAT3 rs1053004 loci are associated with the risk of human TSCC.